Шляхи зміцнення ресурсного потенціалу аграрних підприємств - Волянюк, Вадим Валерійович (My University, 2024)
Визначено, що структура ресурсного потенціалу представлена сукупністю елементів, які можна розглядати у контексті інтерпретації окремих положень теорії факторів виробництва. Розкрито структуру ресурсного потенціалу аграрних підприємств: земля, праця, капітал, інновації, інформація, підприємницький хист, екологія. Обгрунтовано, що зміцнення залежить від підвищення ефективності використання кожного ресурсу окремо та усіх у сукупності разом узятих. It is determined that the structure of resource potential is represented by a set of elements that can be considered in the context of interpreting individual provisions of the theory of production factors. The structure of the resource potential of agricultural enterprises is revealed: land, labor, capital, innovations, information, entrepreneurial talent, ecology. It is substantiated that strengthening depends on increasing the efficiency of using each resource separately and all of them together.
Keywords: кафедра економіки і права; аграрне підприємство; фактори виробництва; потенціал підприємства; resource potential; agricultural enterprise; production factors; enterprise potential; enterprise potential